PROFIL FITOKIMIA DAN BIOAKTIVITAS EKSTRAK DAUN SAWO: SEBUAH ULASAN ILMIAH - Utoro, Panggulu Ahmad Ramadhani; Permatasari, Nelsy Dian; Witoyo, Jatmiko Eko (CHEMTAG Journal of Chemical Engineering, 2024)
The utilization of traditional medicinal plants in Indonesia is an integral part of community medicine practices. Manilkara kauki and Manilkara zapota leaves are medicinal plants that attract attention due to their bioactive compound content and have been used traditionally for a long time. However, scientific reviews of the phytochemical profile and bioactivity of sapodilla leaf extracts, both Manilkara kauki and Manilkara zapota, are still limited. This review aims to discuss in-depth and comprehensively sapodilla leaf extracts, both Manilkara kauki and Manilkara zapota, especially phytochemical profiles and their bioactivity. This scientific review uses a literature study approach with data from 2012-2024 obtained from open-access platforms, especially Google Scholar.  The study results showed that the phytochemical compounds found in the extracts of Manilkara kauki leaves included flavonoids, glycosides, tannins, saponins, steroids/terpenoids, and alkaloids. In contrast, the phytochemicals found in the extracts of Manilkara zapota were flavonoids, tannins, saponins, steroids, terpenoids, and alkaloids. Manilkara kauki leaf extract has many bioactivities including anti-bacterial, anti-diabetic, anti-fungal, antioxidant, and anti-tyrosinase. Meanwhile, Manilkara zapota leaf extract also showed antibacterial, antidiabetic, antioxidant, and anti-diarrhea activities. Further research is needed to optimize the therapeutic potential of these two plants.